Avaliação da remoção de fármacos e desreguladores endócrinos em filtros de polimento para tratamento de esgoto doméstico - Lucas Vassalle de Castro (2017)
This study evaluated the occurrence of eleven micro pollutants classified as pharmacos or endocrine disrupters (ED) present in the final effluent of a large domestic sewage treatment plant using conventional activated sludge technology. In addition, a polishing system basedon filtration and alternative to the commonly used advanced treatment technologies has been proposed to promote the removal of these microcontaminants. The units that composed the proposed polishing system were four columns of sand mixed in the proportion of 90%: 10%by volume of adsorbent materials: column 1 - composed only by sand, column 2 - composed of sand and vermiculite, column 3 - Composed of sand and unactivated charcoal and column 4 - composed of sand and activated charcoal. These units were operated in two differentphases with hydraulic application rates of 16 m³ / m². day and 50 m³ / m²day. The target compounds of this research were: Estrone (E1); 17-estradiol (E2); 17-ethynylestradiol (EE2); Nonylphenol (NP); Octylphenol (OCT); Bisphenol A (BPA); Ibuprofen (IBP), Naproxen (NPX), Diclofenac (DCF), Paracetamol (PCT) and Genfibrozil (GFB). Samples of the effluent treated by the ETE and the polishing unit were subjected to solid phase extraction (SPE) and analyzed by gas chromatography coupled to mass spectrometry (GC / MS) usin the GCMS-QP2010 plus (Shimadzu®) equipment. It was verified the presence of ten of the eleven microcontaminants of this study in the effluent treated by the SWTP evaluated. Among the compounds found, diclofenac is distinguished by the high recurrence of detection in the matrix (85%) and high meanconcentration (~ 17 ng / L). The other drugs and ED detected were: E1; E2; EE2; OCT; BPA; IBP, NPX, PCT and GFB. The only undetected substance was nonylphenol. The average concentrations found in this research are within what has already been reported in the literature. Regarding the polishing columns, a high removal efficiency was observed in the removal of estrogens and naproxen (> 90%), regardless of the operating phase and the filter medium tested. For the other substances, a trend of better removal (30% to 60%) of the drugsand ED was observed when lower surface hydraulic rates were applied. The proposed polishing unit was inefficient to remove the OCT from the effluent treated by the SWTP. For most of the microcontaminants the filter media used did not differ in relation to the level of drug removal and DE, and no column was outstanding in the performance of removal of thesesubstances from the effluent treated by the evaluated SWTP.